The million-dollar baby claims: rethinking birth injuries compensation in the digital age - Mohd Najid, Khadijah; Jahn Kassim, Puteri Nemie (On İki Levha Yayincilik A. Ş., 2019)
The digital age has tremendously affected the practice of medicine. New discoveries and advanced machineries are revolutionizing the healthcare system at an accelerated pace, offering lifesaving innovations and improved operational efficiencies. Consequently, for severely disabled victims of birth injuries, digital healthcare has brought forth technological solutions that offer not only an improved quality of life, but also the ability to lengthen their lifespan. Various assistive technologies and rehabilitation robotics are introduced to aid their independence, bridging gaps between victims and society as well as minimizing the implications of disability. However, the availability of these groundbreaking treatments and issues in life expectancy has led to an exorbitant increase in the amount of compensation demanded by these severely disabled babies to millions of dollars. The notion of restorative justice which the Malaysian tort system upholds requires that the victim be “restored as much as possible to the position prior to the incident” has often been cited as justification in procuring these inflated amount of compensation from the medical providers. The financial burden imposed on the medical providers had led them to subsequently pass on these costs to the society in the form of increased medical prices. This phenomenon is rather worrying as the amount of compensation can escalate further with digital technology moving at a lightning speed and in the long run, the society will eventually suffer. Hence, this paper seeks to discuss the current compensation trend in Malaysia for severely disabled victims of birth injuries and the contemporary issues reflecting the interplay between the developing digital healthcare age and compensation, as well as the possible effects it would bring to the Malaysian healthcare system as a whole.